Global Perspectives on Leadership in Early Childhood Education - Modise, Matshediso Rebecca; Fonsén, Elina; Heikka, Johanna; Phatudi, Nkidi; Bøe, Marit; Phala, Thembi (Helsinki University Press, 2023)
Global Perspectives on Leadership in Early Childhood Education aims to improve leadership and management in Early Childhood Education and Care (ECEC) settings through research evidence. Written for a wide audience, including the academic community, policymakers, practitioners, teachers, directors, and professionals, the book provides knowledge and tools to enhance the ECEC sector. Divided into three thematic sections, the book examines the theory of leadership in ECEC, strategies for improving professional development, and the governance and policies related to ECEC leadership worldwide. In its 16 chapters that blend theoretical and practical perspectives, the book addresses diverse topics, such as pedagogical leadership in different countries, peer mentoring, and the utilization of digital technology in early childhood education. The volume draws upon collaboration through the International Leadership Research Forum in Early Childhood (ILRF-EC) and encompasses contributions from across the world, from South Africa to Norway, Australia, Finland, and beyond. By incorporating different contexts and viewpoints, Global Perspectives on Leadership in Early Childhood Education makes a significant and timely contribution to the field of education.